1979
DOI: 10.1111/j.0954-6820.1979.tb05996.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and Sudden Deaths after Myocardial Infarction

Abstract: ABSTRACT. 1329 patients were discharged alive after acute myocardial infarction initially treated in a CCU. In a five‐year follow‐up, 537 (40%) of the patients died. Routine data registered uniformly during the CCU period showed that, apart from age, the most important factors regarding long‐term prognosis in general were previous ischaemic heart disease and direct or indirect signs of heart failure registered in the CCU. The possibilities to predict sudden death (130 patients died within 2 hours of onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

1980
1980
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…However, when examined in relation to the expected mortality, the effect of age that could be attributed to the MI per se was not found to be significant. This is in contrast to the findings of Kjgller (19) and Helmers & Lundman (9), who both demonstrated a clearly higher relative mortality in MI patients of younger age. Again, a hypothetical explanation could be that present standards of medical and surgical treatment have improved the prognosis in younger patients more than in older coronary heart patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, when examined in relation to the expected mortality, the effect of age that could be attributed to the MI per se was not found to be significant. This is in contrast to the findings of Kjgller (19) and Helmers & Lundman (9), who both demonstrated a clearly higher relative mortality in MI patients of younger age. Again, a hypothetical explanation could be that present standards of medical and surgical treatment have improved the prognosis in younger patients more than in older coronary heart patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The negative effect of the severity of the index MI has not only been documented for the immediate and short-term prognosis, but for late survival as well. As in the present study, evidence of pulmonary congestion has often been found to be an important prognostic factor (2-4, 6,9,12,18,19,22). Although a strict standardization of the clinical observations was not undertaken, the finding that patients noted to have pulmonary crepitations and/or radiological evidence of pulmonary congestion during hospitalization later had twice the mortality as other patients supports the validity of these observations.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several studies have pointed to the feasibility of estimating prognosis after an AM1 (7, 12, 17). However, a number of patients dying early after discharge carry none of the ordinary unfavourable prognostic signs (14). This warrants a search for new prognostic factors that may increase our pre-S .…”
Section: Discussionmentioning
confidence: 99%